The findings of the Industrial Policy Review Group - Sweeney, Paul (Statistical and Social Inquiry Society of Ireland, 1992)
With our extremely high levels of unemployment and the mass emigration in the 1980s, the second highest decade of emigration since Independence, radical and urgent solutions are needed. The problem is awesome but I believe that it can be solved and that the key is industrial policy. I believe that this Report goes a long way in the right direction. What I am less certain of is, if and when its sixty substantive recommendations will be implemented.
Symposium on the Findings of the Industrial Policy Review Group
Read before the Society, 26 March 1992
Keywords: Industrial policy; Economic forecasts; 314.15